Efek Penggunaan Diskon dan Cashback Terhadap Keputusan Pembelian Konsumen pada Media Sosial Shopee - Andriani, Vira (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to analyze the influence of discounts and cashback on consumer purchase decisions on the Shopee e-commerce platform, especially in Pontianak City. Using a quantitative approach with the Partial Least Squares (PLS) analysis technique version 4, this study processed data from respondents who were active users of Shopee who had used the promotion feature. The results of the study show that discounts and cashback have a positive and significant effect on purchase decisions, with cashback having a more dominant influence. In addition, cashback also mediates the effect of discounts on purchase decisions significantly. These findings indicate that consumers tend to respond more to promotions with long-term profits. The implications of these results show the importance of designing a sustainable promotional strategy to increase consumer loyalty and purchase intent in the e-commerce ecosystem.